Ubiquity of the SARS-CoV-2 receptor ACE2 and upregulation in limbic regions of Alzheimer’s disease brain - Zhao, Yuhai; Li, Wenhong; Lukiw, Walter (Folia Neuropathologica, 2021)
The major route of entry for the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) into human host cells is by means of the angiotensin-converting enzyme-2 (ACE2) transmembrane receptor. This zinc-containing carboxypeptidase and membrane-integral surface receptor is ubiquitous and widely expressed in multiple cell types. Hence SARS-CoV-2, an unusually large RNA virus that causes coronavirus disease 2019 (COVID-19) has the remarkable capacity to invade many different types of human host cells simultaneously. Although COVID-19 is generally considered to be primarily an acute respiratory disease SARS-CoV-2 also targets specific anatomical regions of the central nervous system (CNS). In the normal CNS the highest ACE2 levels of expression are found within the medullary respiratory centers of the brainstem and this, in part, may explain the susceptibility of numerous COVID-19 patients to severe respiratory distress. About ~35% of all COVID-19 patients experience neurological and neuropsychiatric symptoms, and a pre-existing diagnosis of Alzheimer’s disease (AD) predicts the highest risk of COVID-19 yet identified, with the highest mortality among elderly AD patients. In the current study of multiple anatomical regions of AD brains compared to age-, post-mortem interval- and gender-matched controls (n = 10 regions, n = 32 brains), ACE2 expression was found to be significantly up-regulated in AD in the occipital lobe, temporal lobe neocortex and hippocampal CA1. The temporal lobe and hippocampus of the brain are also targeted by the inflammatory neuropathology that accompanies AD, suggesting a significant mechanistic overlap between COVID-19 and AD, strongly centered on invasion by the neurotropic SARS-CoV-2 virus via the increased presence of ACE2 receptors in limbic regions of the AD-affected brain.